Competing on price, speed, and reliability: How does bounded rationality matter?. Issue 9 (2nd September 2021) - Jalili Marand, Ata; Li, Hongyan; Thorstenson, Anders
Abstract: A firm's delivery performance may have significant impact on the satisfaction and purchase behaviour of its customers. Empirical evidence has shown that customers are willing to pay a higher price for a faster and more reliable service. In this study, we address the interactions between the price, promised delivery time, and delivery-reliability level in a competitive setting. We model the problem as a competition among an arbitrary number of profit-maximizing firms facing boundedly rational customers who can choose to buy the service from one of the firms or balk. We prove the existence of a unique Nash equilibrium and propose a simple iterative algorithm that converges to the equilibrium. Furthermore, we compare our results with those in the existing literature and report interesting managerial insights. Our results suggest that having a clear understanding of customers' bounded rationality level is crucial for businesses to determine their optimal decisions and position in the market both in monopolistic and competitive settings.